Quantitative HPLC and FTIR-based metabolomics for clustering Centella asiatica cultivation ages and evaluation of their radical scavenging activity - Rafi, Mohamad; Anastasia Grandivoriana Nomi; Dewi Anggraini Septaningsih; Heryanto, Rudi; Sastia Prama Putri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Centella asiatica is a medicinal plant used to treat stomachache, cough, sore throat, blood booster, and skin diseases. The difference in harvesting time is among the factors that can significantly affect the chemical composition of C. asiatica. The purpose of this study was to evaluate the difference of C. asiatica cultivation ages through a metabolomics (targeted and untargeted) analysis using FTIR spectra, HPLC analysis of four main components, and evaluation of its radical scavenging activity. The results showed that differences in cultivation ages affected the chemical composition of C. asiatica. It was shown by the FTIR spectrum indicating the vibration of several functional groups such as OH, C-H, C=O, C=C, C-O, C-N, C-O phenol, and alkyl halides with differences in their intensities. The results of the HPLC showed that C. asiatica harvested after four months post-planting (MPP) had the highest content of madecassoside, asiaticoside, madecassic acid, and asiatic acid, respectively. A principal component analysis (PCA) was carried out to clustering C. asiatica based on its cultivation ages. The PCA results showed that each sample could be grouped with a total variance of the first two principal components (PC) using peak are of the four main components analyzed by HPLC and absorbance at wavenumber 400-4000 cm-1 from FTIR spectra were 98% and 95%, respectively. The radical scavenging activity demonstrated that the 4 MPP had the highest inhibition of about 53.81±0.92 %. So, C. asiatica at 4 MPP gave optimum level four main metabolite content and radical scavenging activity.